2018
DOI: 10.1042/bcj20180016
|View full text |Cite
|
Sign up to set email alerts
|

Heme degradation enzyme biliverdin IXβ reductase is required for stem cell glutamine metabolism

Abstract: Bioenergetic requirements of hematopoietic stem cells and pluripotent stem cells (PSCs) vary with lineage fate, and cellular adaptations rely largely on substrate (glucose/glutamine) availability and mitochondrial function to balance tricarboxylic acid (TCA)-derived anabolic and redox-regulated antioxidant functions. Heme synthesis and degradation converge in a linear pathway that utilizes TCA cycle-derived carbon in cataplerotic reactions of tetrapyrrole biosynthesis, terminated by NAD(P)H-dependent biliverdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Whereas aggregate data demonstrated that equivalent numbers of transcripts were up‐ ( N = 1008) or down‐regulated ( N = 1196), DEFA3 and HBG1/2 displayed < 2‐fold change over time. There were no differences in D0/D5 platelet phenotypic markers JC1 (viability marker of mitochondrial potential), 56 CD41 + , or CD41 + /Annexin V + events, excluding that transcriptomic differences were caused by cell death and RNA degradation (Figure 5G). These data establish that (1) for a subset of genes displaying concordantly abundant RiboSeq and RNA expression patterns, ribosomal occupancy selectively shapes and regulates transcript decay in CB platelets, and (2) DEFA3 and HBG1/2 retain abundance characteristics as stable biomarkers for neonatal platelet detection in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas aggregate data demonstrated that equivalent numbers of transcripts were up‐ ( N = 1008) or down‐regulated ( N = 1196), DEFA3 and HBG1/2 displayed < 2‐fold change over time. There were no differences in D0/D5 platelet phenotypic markers JC1 (viability marker of mitochondrial potential), 56 CD41 + , or CD41 + /Annexin V + events, excluding that transcriptomic differences were caused by cell death and RNA degradation (Figure 5G). These data establish that (1) for a subset of genes displaying concordantly abundant RiboSeq and RNA expression patterns, ribosomal occupancy selectively shapes and regulates transcript decay in CB platelets, and (2) DEFA3 and HBG1/2 retain abundance characteristics as stable biomarkers for neonatal platelet detection in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Cells were expanded in SFEM II medium for 24–48 h prior to terminal MK differentiation using serum‐free SFEM containing MK expansion supplement CC220 (STEMCELL Technologies). Differentiation was monitored by flow cytometry, gating on live 7‐actinomycin D (7‐AAD)‐negative cells for immunophenotypic quantification of CD41a (integrin α IIb , MK), Annexin V as a marker of PS exposure and apoptosis, 34,36 or JC1 (Thermo Fisher) as a sensitive marker of mitochondrial membrane potential (ΔΨm) 37,38 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gln and Glu are known ingredients for the heme biosynthesis pathway, and defective Gln metabolism was also observed in heme degradation enzyme BLVRB -knockout cells. 24 We therefore hypothesized that SETD1A-deficient cells may have lower consumption of these metabolites ( Figure 3G ). To examine the role of the heme biosynthesis pathway in Gln accumulation, we evaluated Gln levels in COX15 - or HMBS -knockout cells.…”
Section: Resultsmentioning
confidence: 99%
“…Being reported to be significantly up-regulated in different cancers [54], it is also induced by rosiglitazone [55], an anti-diabetic drug, a derivative of troglitazone, that we found. Enrichment analysis also suggests a response to hypoxia and oxidative stress by HYOU1, MVP, GSTM2, quinone oxidoreductase-like protein 1, TST, BLVRB, and PRDX1 up-regulation in cells exposed to soil extracts (DxCS), as well as BLVRB related to heme degradation [56][57][58]. Interestingly, atrazine could be the cause of the observed oxidative stress [49].…”
Section: Discussionmentioning
confidence: 96%